Fuzzy Logic Control of Wind Turbine Storage System Connected to the Grid Using Multilevel Inverter - Ali Berboucha (International Journal of Energetica)
This paper aimed to evaluate the use of wind turbine storage systems to provide electricity in the electrical grid through a five-level inverter. The proposed system is composed of four wind turbine generators based on permanent magnet synchronous generator (PMSG), four battery storage systems connected to each capacitor of the DC link and a five level diode clamped inverter connected to the grid by three phase transformer. The control algorithm proposed is based on fuzzy logic to tracks and extract the maximum wind power by controlling the rotational speed of wind turbine, which is most appropriate when there is a lack of information on the characteristic Cp (λ,β) of the turbine. The system operator controls the power production of the four wind turbine generators by sending out reference power signals to each input side regulation unit, the input side regulation units regulate the voltage of each capacitor of the DC link, regulate the voltage and the state of charge of each battery storage system. The inverter is controlled by simplified space vector modulation which allows us to reduce the computational time and reduce the algorithm complexity compared to the conventional five levels space vector modulation, the grid side control level regulate the power and the current injected to the grid.